Republic of Armenia : 2017 Article IV Consultation and Fifth and Final Review Under the Extended Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Armenia's growth has been satisfactory with inflation under control, the fiscal situation broadly well managed, and foreign exchange reserves enhanced. In 2016, GDP growth was only 0.2 percent, deflationary pressures persisted, and the fiscal deficit rose to 5.6 percent of GDP. Economic activity in 2017 has shown signs of recovery, accompanied by a pickup in inflation and private sector credit growth, supported by monetary policy easing. With improving outlook in major trading partners and a pickup in private sector activity, real GDP is projected to grow by about 3 percent in 2017, while inflation would reach about 2 percent by end-2017.